Model fitness on emotional intelligence, personality trait and leadership behavior on job performances - Md Nawi, Nurul Hudani; Redzuan, Ma’rof; Hamsan, Hanina Halimatusaadiah; Asim, Ibrani Adam (Penerbit UTM Press, 2013)
The main objective of this cross-sectional study is to determine the correlation of emotional intelligence and personality trait as well as the fitness of suggestion hypothetical model and sample data among school educator leaders in High Performance Schools (SBT). Four sets of questionnaire to measure emotional intelligence, personality trait, leadership behavior and work performance were administered to 306 (89%) subjects in 15 SBT schools in Malaysia. The finding by the bivariate analysis using the Pearson correlation method indicates that the personality trait such as Conscientiousness (r=.552, p<.05),Openness to experiences (r=.362, p<.05), Extraversion (r=.505, p<.05), Agreeableness (r=.193, p<.05) are positively and significant correlated with overall emotional intelligence. Moreover, the results indicate an adequate fit and it obviously met the basic requirement of model fit. Therefore, the modification model is significantly improves the fit of the model to the data. On a practical note, the assessment of psychological construct in schools setting could possibly assist in enhancing the work performances in delivering huge benefits to the society especially in the educational contexts.